2009
DOI: 10.1080/10401330802573910
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership and Team Behavior on Standard of Care Delivered During Human Patient Simulation: A Pilot Study for Undergraduate Medical Students

Abstract: The methods used provide a possible method for training and assessing team performance during simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Four studies (5%) applied the assessment tool to standardized videos with actors playing all members of the HCA team and thus did not include trainees or learners as study participants. 67,68,109,110 Of the 83 included studies, 29 (35%) assessed leadership at the individual level, whereas 53 (64%) assessed it at the team level (see Supplemental Digital Tables 2 and 3 at http://links.lww. com/ACADMED/A295 for a list of the leadership behaviors or styles assessed, by tool).…”
Section: Assessment Tool Applicationmentioning
confidence: 99%
“…Four studies (5%) applied the assessment tool to standardized videos with actors playing all members of the HCA team and thus did not include trainees or learners as study participants. 67,68,109,110 Of the 83 included studies, 29 (35%) assessed leadership at the individual level, whereas 53 (64%) assessed it at the team level (see Supplemental Digital Tables 2 and 3 at http://links.lww. com/ACADMED/A295 for a list of the leadership behaviors or styles assessed, by tool).…”
Section: Assessment Tool Applicationmentioning
confidence: 99%
“…The effect sizes calculated are shown in Table 1 and Table 2. They range from very high (r¼0.77) 42 to small (r¼20.02). 48 Only one study reported a small effect, 48 while all the others described effects considered as large or medium.…”
Section: Effects Of Team Processes On Performance In the Non-intervenmentioning
confidence: 99%
“…The American College of Surgeons recommends integration of simulation as a means to enhance patient safety, reduce medical errors, and evaluate various competencies. Previous studies support the use of curriculum-based simulation with computerized mannequins, live animals, and/or cadavers to hone individual decision-making, leadership, and communication skills as well as improve team performance during critical care scenarios [24][25][26][27]. Human patient simulators can be employed as an evaluation tool to objectively assess resident performance and knowledge related to critical care [20,28,29].…”
Section: Discussionmentioning
confidence: 99%